O grupo "cotidiano e universidade" para estudantes autistas: uma análise da prática de terapia ocupacional - Gutierrez, Ana Clara; Dias, Lívia Maria Simões (Universidade Federal de São Carlos, 2025)
This study presents a critical analysis of the practice developed within the extension group “Everyday Life and University for Autistic Students,” offered by the Federal University of São Carlos (UFSCar). The group aimed to address the desires and needs of autistic university students and to promote a space for social interaction, experimentation, and care. The research method consists of a Critical Practice Analysis, constructed from systematic records of the meetings and grounded in the framework of the Dynamic Occupational Therapy Method (MTOD). Sixteen students from different programs participated in the initiative, seven of whom attended consistently. The activities were collaboratively defined and guided by the needs and desires expressed by the participants themselves. Three experiences were highlighted: the Collective Body Map, the Theatre of the Oppressed activity, and self-massage using sensory balls, all of which were described in the intervention process. The analysis revealed that the group’s facilitation emphasized sensitive listening, collective construction, and openness to the unpredictable, valuing students’ singularities and the production of meaning in the here-and-now. The activities functioned as devices for reflection, strengthening bonds, and fostering engagement, configuring a space of care and health promotion within the university context. It is concluded that the practice examined contributes to the advancement of occupational therapy actions directed toward this population, offering support for policies and interventions that promote inclusion and student retention.
"Everyday life and university" group for autistic students: an analysis of an occupational therapy practice
Keywords: Terapia Ocupacional; Saúde Mental; Autismo; Universidade; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar; 4. Educação de Qualidade